PENGARUH KOMPENSASI FINANSIAL TERHADAP KINERJA PEGAWAI HARIAN LEPAS DI DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PALEMBANG - Susi Handayani (Jurnal Ilmiah Ekonomi Global Masa Kini)
Results of hypothesis testing has proven there are significant financial compensation to performance phl t-test, it is known that the t value in the variable Financial compensation is greater than t table (7.324> 1.994). This shows that the hypothesis of Ha Ho accepted and rejected, then this proves that there is an influence on the performance of financial compensation by proving that there are significant financial compensation to the performance by the probability (Sig.) Of 0.000 <0.05. Results of hypothesis testing based on the research results known financial compensation variable positive and significant effect on the performance with a percentage of 4.41% and 3.41% influenced by other variables that are not analyzed in this study. Financial compensation is predominantly influenced by salaries, because the salaries phl can meet the needs of the physical and social status so phl will gain job satisfaction. Performance is very dominantly influenced by the award given in the form of money, because phl will feel the results of the work they provide is greatly appreciated by the remuneration and phl will feel comfortable with their work. Keywords: PHL, Financial Compensation, Performance